2016
DOI: 10.1053/j.gastro.2016.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Cancer Stage and Treatment Differences on Racial Disparities in Survival From Colon Cancer: A United States Population-Based Study

Abstract: Background & Aims We evaluated differences in treatment of black vs white patients with colon cancer and assessed their effects on survival, based on cancer stage. Methods We collected data from the Surveillance, Epidemiology and End Results (SEER)-Medicare database and identified 6190 black and 61,951 white patients with colon cancer diagnosed from 1998 through 2009 and followed through 2011. Three sets of 6190 white patients were sequentially matched, using a minimum distance strategy, to the same set of 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(90 citation statements)
references
References 60 publications
2
87
1
Order By: Relevance
“…Although black patients are less likely than others to receive appropriate surgery, adjuvant chemotherapy, and radiation treatments, survival is lower in black than in white patients even when treatment is equal . A recent study found that tumor presentation at diagnosis played a larger role in survival differences than treatment, estimating that 40% of the racial disparity in colon cancer survival is because of the combined effects of later stage at diagnosis, a higher likelihood of unfavorable tumor characteristics, and more comorbidities among black patients . Survival disparities are also evident within racial and ethnic groups.…”
Section: Selected Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although black patients are less likely than others to receive appropriate surgery, adjuvant chemotherapy, and radiation treatments, survival is lower in black than in white patients even when treatment is equal . A recent study found that tumor presentation at diagnosis played a larger role in survival differences than treatment, estimating that 40% of the racial disparity in colon cancer survival is because of the combined effects of later stage at diagnosis, a higher likelihood of unfavorable tumor characteristics, and more comorbidities among black patients . Survival disparities are also evident within racial and ethnic groups.…”
Section: Selected Findingsmentioning
confidence: 99%
“…50 A recent study found that tumor presentation at diagnosis played a larger role in survival differences than treatment, estimating that 40% of the racial disparity in colon cancer survival is because of the combined effects of later stage at diagnosis, a higher likelihood of unfavorable tumor characteristics, and more comorbidities among black patients. 51 Survival disparities are also evident within racial and ethnic groups. For example, blacks who are privately insured are 46% more likely…”
Section: Subsite Distributionmentioning
confidence: 99%
“…). Racial disparities in CRC survival largely reflect differences in treatment, SES, comorbidities, and tumor characteristics . Numerous studies have documented that blacks with CRC are less likely than whites to receive recommended surgical treatment, radiation, and chemotherapy .…”
Section: Selected Findingsmentioning
confidence: 99%
“…Finally, stage IV colon cancer is divided into stages IVA and IVB. 10,11 Table 1 provides the descriptions of all these stages. Per recent investigations, 5-year survival rates are .90% for stage I CRC and ,10% for stage IV CRC.…”
Section: Stages Of Crcmentioning
confidence: 99%